Efektivitas Media Pembelajaran Blooket dalam Meningkatkan Hasil Belajar IPS Siswa SMP - Sihite, Novita Sari Elisabet; Safitri, Desy; Saipiatuddin (Edukasi IPS, 2025)
The integration of technology in education has become an important strategy to improve students’ learning outcomes, one of which is through the use of digital learning media. The implementation of digital learning media creates a classroom atmosphere that is not passive and encourages students’ enthusiasm in the learning process. This study aims to determine the effect of using Blooket learning media on the learning outcomes of Grade VIII students at SMP Negeri 92 Jakarta in the Social Studies (IPS) subject. The research employed a quantitative method with a quasi-experimental design using a pre-test and post-test control group. The sample consisted of 40 students who were divided into an experimental class (using Blooket) and a control class (conventional learning). he instrument used was a 32-item multiple-choice test. The research hypothesis was tested using a paired t-test; if the sig. (2-tailed) value is < 0.05, then there is a significant difference between the learning outcomes in the pre-test and post-test data, which was 0.000. The results show that the experimental class experienced a greater improvement in learning outcomes (from a mean score of 81 to 92) compared to the control class (from 85 to 91). These findings indicate that the use of Blooket has a significant positive effect on students’ learning outcomes in Social Studies.